RANCANG BANGUN SISTEM INFORMASI EVALUASI SISWA DAN KEHADIRAN GURU BERBASIS WEB - Ahmad Yani; Beni Saputra; Redaksi Tim Jurnal (PETIR, 2018)
The information system of student assessment results and the presence of teachers is the most important component in building the school's academic system. With the application of information systems evaluating student grades and teacher attendance, the school can process data related to academic information which includes data on students, teachers, education, subjects, absences, classes, departments, years of teaching, grades, schedule of lessons. he student evaluation information system and teacher absenteeism can be the main points most needed by schools in managing each student's grades and the presence of each teacher. Without an information system on the value and presence of teachers, the school will be very difficult in getting report cards and reports on teacher attendance during teaching. Student evaluation information system and teacher attendance are designed web-based with the method of developing the waterfall system. With the information system evaluation of student evaluations and teacher attendance, it is expected to be able to provide better service to students, teachers and parents in getting information about the value and presence of teachers at the school.